Effects on impulsivity and delay discounting of intermittent theta burst stimulation add-on to dialectical behavioral therapy in borderline personality disorder: a randomized, sham-controlled pilot trial - Milenko Kujovic; Christian Bahr; Mathias Riesbeck; Daniel Benz; Martina Deiß; Zsofia Margittai; Sebastian Henges; Dirk Reinermann; Christian Plewnia; Eva Meisenzahl (Borderline Personality Disorder and Emotion Dysregulation)
Abstract Background Dialectical behavioral therapy (DBT) and repetitive transcranial magnetic stimulation (rTMS) are both effective in treating borderline personality disorder (BPD). Impulsivity and impaired decision-making are prominent features of BPD, and therapeutic interventions targeting these symptoms could lead to significant improvements. Objective/Hypothesis We hypothesized that intermittent theta burst stimulation (iTBS), a modified rTMS protocol that targets the left dorsolateral prefrontal cortex, would enhance the therapeutic effects of DBT, leading to greater improvements in impulsivity and decision-making compared with sham stimulation. Methods We performed a single-blind, randomized, sham-controlled pilot study to evaluate the efficacy of iTBS as an add-on to an 8-week DBT program for BPD in a routine inpatient setting. A total of 53 BPD patients were randomly assigned to receive either iTBS (n = 25) or sham stimulation (n = 28) during weeks 4 to 8 of DBT, and 36 patients met the inclusion criteria for the present analysis (≥ 16 of 20 iTBS/sham sessions and assessment of delay discounting). The study endpoints were the Barratt Impulsiveness Scale-15 for impulsivity and the Monetary Choice Questionnaire for decision-making/delay discounting. Results A mixed model repeated measures analysis with a 2 × 2 factorial between-subjects design showed a significant overall improvement over time in impulsivity but not in decision-making/delay discounting. No significant differences were found between iTBS and sham, although post hoc tests revealed significant changes in impulsivity in the iTBS group (meandiff = -4.7, p = .001, Cohen’s d = 0.68) but not in the sham group (meandiff = -2.1, p = .077, d = 0.31). Conclusions iTBS may offer long-term benefits as an add-on treatment to DBT for impulsivity in BPD, suggesting the need for further investigation in larger-scale studies. Trial registration Registered at drks.de (no. DRKS00020413) on January 13, 2020.